High-performance biomass hard carbon and bio-enzyme pretreatment preparation method and application thereof

The content of cellulose, hemicellulose and lignin in biomass raw materials is regulated through biological enzyme pretreatment, and the problem of unstable hard carbon performance caused by different biomass raw materials is solved, and high-performance biomass hard carbon is prepared, suitable for sodium ion battery negative electrode materials.

CN119898749AActive Publication Date: 2025-04-29SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411880484.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-29
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The performance of hard carbon production products is unstable due to the differences in cellulose, hemicellulose and lignin content in different biomass raw materials.

Method used

The biological enzyme pretreatment method is adopted to regulate the relative content of the three major proteins in the biomass raw materials through enzymatic pretreatment of biological enzymes such as cellulase, hemicellulase and laccase, and high-performance biomass hard carbon is prepared through high-temperature carbonization and pickling.

Benefits of technology

It realizes the stability and controllability of the performance of biomass hard carbon products, improves its reversible capacity and first-circle Coulomb efficiency, and is suitable for sodium ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898749A_ABST
    Figure CN119898749A_ABST
Patent Text Reader

Abstract

The invention discloses high-performance biomass hard carbon as well as a bio-enzyme pretreatment preparation method and application thereof, and belongs to the field of sodium ion batteries. The bio-enzyme pretreatment preparation method of the high-performance biomass hard carbon comprises the following steps: cutting and crushing a biomass raw material, and cleaning and purifying the biomass raw material; adding the cleaned biomass powder into a solution containing biological enzyme for enzymolysis pretreatment; the biomass powder subjected to enzymolysis pretreatment is filtered and taken out, the biomass powder is placed in a large atmosphere furnace to be subjected to high-temperature carbonization after being dried, then the carbonized powder is subjected to acid pickling and drying, and the high-performance biomass hard carbon is obtained. Through a green and efficient biological enzyme pretreatment process, the relative content of cellulose, hemicellulose and lignin in the biomass raw material is regulated and controlled, the microprocess of carbonization is influenced, the biomass hard carbon material with a stable structure is prepared, and meanwhile, the reversible capacity and the first-circle coulombic efficiency of the biomass hard carbon material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a high-performance biomass hard carbon and a preparation method and application thereof through bioenzyme pretreatment. Background Art

[0002] With the acceleration of global energy transformation and the vigorous development of electric vehicles, energy storage systems and other fields, the battery industry has ushered in an unprecedented period of rapid development. Among them, the market demand for secondary batteries as core components has shown a trend of rapid growth. In this context, although lithium-ion batteries have long dominated the market with their advantages such as high energy density and long cycle life, in recent years, with the dual pressure of resource constraints and environmental protection needs, sodium-ion batteries, as a powerful supplement to lithium-ion batteries, are gradually returning to people's vision and receiving widespread attention.

[0003] The history of sodium-ion batteries can be traced back to the early 1980s, when it was initially explored as a potential energy storage technology. However, with the rapid iteration of lithium-ion battery technology and the continuous optimization of its performance, especially the significant progress in energy density and cycle stability, the research and development of sodium-ion batteries once stagnated. This situation has undergone a fundamental change since 2010. With the explosive growth of the new energy vehicle industry, the market demand for power batteries has expanded sharply, resulting in tight supply of key raw materials for lithium-ion batteries such as lithium and cobalt, and rising costs. This has rekindled the fire of hope for the research of room-temperature sodium-ion batteries.

[0004] Although the commercialization process of sodium-ion batteries started late, its unique advantages, such as abundant resources, low cost and environmental friendliness, make it an important option in the future energy storage field. However, the current commercial application of sodium-ion batteries still faces many challenges, among which the high cost of negative electrode materials is one of the key factors restricting its development. At present, hard carbon is the first choice for negative electrode materials of sodium-ion batteries, and its precursors are varied, including biomass precursors, sugar precursors, synthetic resin precursors and asphalt precursors. Among these options, biomass materials, such as coconut shells, straw, corn cobs and other agricultural and forestry wastes, are regarded as the preferred materials for the preparation of high-performance hard carbon because of their high carbon content, wide source of raw materials and low price.

[0005] However, due to the large differences in the cellulose, hemicellulose and lignin content between different biomass raw materials, the prepared biomass hard carbon products lack stability, and also have a great impact on the stability and controllability of the industrial production process. Therefore, how to maintain the controllable stability of the biomass hard carbon preparation process between different biomass precursor raw materials while improving the technical level of biomass hard carbon has become a hot spot and difficulty in the current sodium ion battery research field. Summary of the invention

[0006] In view of the problems and shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing high-performance biomass hard carbon by enzyme pretreatment, aiming to solve the problem of unstable performance of hard carbon production products caused by differences in cellulose, hemicellulose and lignin content in different biomass raw materials.

[0007] To achieve the above object, the present invention proposes a method for preparing high-performance biomass hard carbon by enzyme pretreatment, which comprises the following specific steps:

[0008] I: cutting and crushing the biomass raw materials, and then cleaning and purifying them;

[0009] II: adding the washed biomass powder into a solution containing biological enzymes for enzymatic pretreatment;

[0010] III: The biomass powder after enzymatic pretreatment is filtered out, dried and then carbonized at high temperature, and then the carbonized powder is acid-washed and then dried to obtain high-performance biomass hard carbon.

[0011] According to some embodiments of the present application, the biomass raw material is at least one of various biomass raw materials with different cellulose, hemicellulose and lignin contents such as bamboo, beech, eucalyptus, straw, rice stalks, and fruit shells.

[0012] According to some embodiments of the present application, the biomass raw material needs to be ground and pulverized, and the pulverized particle size needs to be less than 50 mesh.

[0013] According to some embodiments of the present application, the biomass raw material powder needs to be cleaned and purified, and the cleaning solution is at least one of water, ethanol, petroleum ether, and hydrochloric acid.

[0014] According to some embodiments of the present application, the biological enzyme includes at least one of cellulase, hemicellulase, laccase, pectinase, catalase, and amylase.

[0015] According to some embodiments of the present application, the biological enzyme is a combination of cellulase, hemicellulase and laccase, specifically: cellulase, hemicellulase and laccase are used in sequence for enzymatic hydrolysis, and the conditions for cellulase, hemicellulase and laccase treatment are: enzymatic hydrolysis at 25°C-60°C for 6h-72h.

[0016] According to some embodiments of the present application, the biological enzyme needs to be dissolved in a corresponding solution, which is a sodium citrate buffer with a pH between 4-8, preferably a pH of 5-7, more preferably a pH of 5-6, and most preferably a pH of 6.0.

[0017] According to some embodiments of the present application, the enzymolysis temperature is 25°C-60°C, preferably the enzymolysis temperature is 45°C.

[0018] According to some embodiments of the present application, the enzymatic hydrolysis time is 6 h to 72 h.

[0019] According to some embodiments of the present application, when the biological enzyme is cellulase, the enzymatic hydrolysis time is greater than 24 hours, preferably 24-48 hours; when the biological enzyme is hemicellulase, the enzymatic hydrolysis time is preferably greater than 12 hours; when the biological enzyme is laccase, the enzymatic hydrolysis time is preferably greater than 12 hours.

[0020] According to some embodiments of the present application, the enzymatic pretreatment environment needs to control the solid-liquid ratio, and the solid-liquid ratio is 1:3 to 1:10 (g / mL), and preferably the solid-liquid ratio is 1:5 (g / mL).

[0021] According to some embodiments of the present application, the high-temperature carbonization temperature is 1200-1500°C, the carbonization time is 2-6h, and the carbonization atmosphere is one or more of nitrogen and argon; preferably, the carbonization temperature is 1400°C, and the carbonization time is 3h.

[0022] According to some embodiments of the present application, the pickling solution is a 1 mol / L hydrochloric acid solution, and the pickling time is 6-12 h.

[0023] Another object of the present invention is to provide a high-performance biomass hard carbon prepared by the above method.

[0024] The high-performance biomass hard carbon has a first-cycle coulombic efficiency greater than 90%, and a reversible capacity between 300-380 mAh / g.

[0025] Another object of the present invention is to propose the use of the high-performance biomass hard carbon material as a negative electrode for sodium ion batteries.

[0026] According to some embodiments of the present invention, a negative electrode slurry is prepared using a high-performance biomass hard carbon material: conductive agent: binder (8:1:1), which is coated on a copper foil and then dried and sliced, and a sodium ion battery is obtained by assembling the remaining components.

[0027] Compared with the prior art, the technical features and advantages of the present invention are as follows:

[0028] As the raw material for hard carbon synthesis, the carbon source in the biomass precursor is mainly composed of cellulose, hemicellulose and lignin. However, there are often large differences in the content of the three major elements in different biomass raw materials, which makes the biomass hard carbon materials prepared by carbonizing different biomass raw materials often have large differences in structure and performance. The present invention adopts a green, environmentally friendly and efficient bio-enzyme pretreatment method, by performing enzymatic pretreatment on the biomass raw materials, selectively etching one or more of the cellulose, hemicellulose and lignin components in the biomass raw materials by bio-enzymes such as cellulase, hemicellulose, laccase, etc., further controlling the relative content of the three major elements in the biomass raw materials, regulating the carbonization process, and at the same time, by optimizing the enzymatic environment and changing key parameters such as pH, the enzymatic efficiency and degree of enzymatic hydrolysis are greatly improved, thereby stably and controllably preparing high-performance biomass hard carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly explain the technical solutions adopted by the embodiments of the present invention or the prior art, the drawings involved in the embodiments or the prior art description are briefly introduced below. It should be noted that these drawings only represent some embodiments of the present invention, and those skilled in the art can derive other related drawings based on these drawings without creative efforts.

[0030] Figure 1 This is a charge and discharge curve diagram of the sodium ion battery of Example 4 of the present invention, and the experimental results are all stable data repeated three times;

[0031] Figure 2 This is a charge and discharge curve diagram of the sodium ion battery of Example 8 of the present invention, and the experimental results are all stable data repeated three times;

[0032] Figure 3 This is a charge and discharge curve diagram of the sodium ion battery of Example 13 of the present invention, and the experimental results are all stable data repeated three times;

[0033] Figure 4 This is a charge and discharge curve diagram of the sodium ion battery of Example 16 of the present invention. The experimental results are all stable data repeated three times.

[0034] Figure 5 This is a charge and discharge curve diagram of the sodium ion battery of Comparative Example 1 of the present invention. The experimental results are all stable data repeated three times.

[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] In order to clearly show the objectives, technical solutions and advantages of the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be fully and accurately described below. It should be clear that the following examples are only used to illustrate the present invention, rather than to limit it. Unless otherwise explicitly stated, all technical terms and scientific terms used herein follow the common definitions in the technical field, and the reagents mentioned all reach industrial or analytical purity standards. In addition, the drawings and descriptions provided are intended to help those skilled in the art to have a deeper understanding of the present application, rather than to limit the subject matter covered by the claims.

[0037] As used herein, "ranges" are defined by setting lower limits and upper limits, which define the boundaries of a particular range. Such ranges may or may not include their end values ​​and may be freely combined, i.e., any lower limit may be combined with any upper limit to form a new range.

[0038] Unless otherwise specified, all embodiments and optional solutions in this application can be combined with each other to create new technical solutions. Similarly, unless otherwise specified, all technical features and optional features in this application can also be combined with each other to form new technical solutions.

[0039] The present invention is described in detail below, which comprises the following specific steps:

[0040] I: cutting and crushing the biomass raw materials, and then cleaning and purifying them;

[0041] II: adding the washed biomass powder into a solution containing biological enzymes for enzymatic pretreatment;

[0042] III: The biomass powder after enzymatic pretreatment is filtered out, dried and placed in a large atmosphere furnace for high-temperature carbonization, and then the carbonized powder is acid-washed and dried to obtain high-performance biomass hard carbon.

[0043] Preferably, the beech wood biomass raw material in step I has a grinding particle size of less than 50 mesh.

[0044] Preferably, the biological enzyme used in step II is one or more of cellulase, hemicellulase, and laccase, the enzymatic hydrolysis temperature is 45° C., the enzymatic hydrolysis time is 6-72 h, and the pH of the enzymatic hydrolysis solution is 6.0.

[0045] Preferably, in step III, nitrogen is used as the carbonization atmosphere, the carbonization temperature is 1400° C., and the carbonization time is 3 hours.

[0046] The present invention is described in further detail below in conjunction with embodiments:

[0047] The biological enzymes used in this application were purchased from Shanghai Yuanye Biotechnology Co., Ltd. without any additional treatment.

[0048] Example 1

[0049] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then washed and purified with water and ethanol in turn;

[0050] II: Add the cleaned beech wood powder into a solution containing cellulase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 6 hours of enzymatic hydrolysis.

[0051] III: The beech wood powder after enzymatic pretreatment is dried and placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed with a 1 mol / L hydrochloric acid solution and then dried to obtain high-performance biomass hard carbon.

[0052] Example 2

[0053] The preparation process of Example 2 is basically the same as that of Example 1, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 12 hours.

[0054] Example 3

[0055] The preparation process of Example 3 is basically the same as that of Example 1, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 24 hours.

[0056] Example 4

[0057] The preparation process of Example 4 is basically the same as that of Example 1, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 48 hours.

[0058] Example 5

[0059] The preparation process of Example 5 is basically the same as that of Example 1, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 72 hours.

[0060] Example 6

[0061] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then washed and purified with water and ethanol in turn;

[0062] II: Add the cleaned beech wood powder into a solution containing hemicellulase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 6 hours of enzymatic hydrolysis.

[0063] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0064] Example 7

[0065] The preparation process of Example 7 is basically the same as that of Example 6, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 12 hours.

[0066] Example 8

[0067] The preparation process of Example 8 is basically the same as that of Example 6, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 24 hours.

[0068] Example 9

[0069] The preparation process of Example 9 is basically the same as that of Example 6, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 48 hours.

[0070] Example 10

[0071] The preparation process of Example 10 is basically the same as that of Example 6, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 72 hours.

[0072] Embodiment 11

[0073] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then washed and purified with water and ethanol in turn;

[0074] II: Add the cleaned beech wood powder into a solution containing laccase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 6 hours of enzymatic hydrolysis.

[0075] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0076] Example 12

[0077] The preparation process of Example 12 is basically the same as that of Example 11, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 12 hours.

[0078] Embodiment 13

[0079] The preparation process of Example 13 is basically the same as that of Example 11, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 24 hours.

[0080] Embodiment 14

[0081] The preparation process of Example 14 is basically the same as that of Example 11, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 48 hours.

[0082] Embodiment 15

[0083] The preparation process of Example 15 is basically the same as that of Example 11, except that the enzymatic hydrolysis time in step II of preparing high-performance biomass hard carbon is extended to 72 hours.

[0084] Example 16

[0085] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then washed and purified with water and ethanol in turn;

[0086] II: Add the washed beech wood powder to a solution containing cellulase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 48 hours of enzymolysis. Then, add the beech wood powder pretreated with cellulase to a solution containing hemicellulase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and enzymolysis for 24 hours. Finally, add the beech wood powder pretreated with cellulase and hemicellulase to a solution containing laccase (sodium citrate buffer with a pH of 6.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and enzymolysis for 24 hours.

[0087] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0088] Comparative Example 1

[0089] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then cleaned and purified;

[0090] II: The cleaned beech wood powder is dried and placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0091] Comparative Example 2

[0092] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then cleaned and purified;

[0093] II: Add the cleaned beech wood powder into a solution containing cellulase (sodium citrate buffer with a pH of 4.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 48 hours of enzymatic hydrolysis.

[0094] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0095] Comparative Example 3

[0096] The preparation process of Comparative Example 3 is basically the same as that of Comparative Example 2, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 7.0.

[0097] Comparative Example 4

[0098] The preparation process of Comparative Example 3 is basically the same as that of Comparative Example 2, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 8.0.

[0099] Comparative Example 5

[0100] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then cleaned and purified;

[0101] II: Add the cleaned beech wood powder into a solution containing hemicellulase (sodium citrate buffer with a pH of 4.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 24 hours of enzymatic hydrolysis.

[0102] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0103] Comparative Example 6

[0104] The preparation process of Comparative Example 6 is basically the same as that of Comparative Example 5, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 7.0.

[0105] Comparative Example 7

[0106] The preparation process of Comparative Example 7 is basically the same as that of Comparative Example 5, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 8.0.

[0107] Comparative Example 8

[0108] I: 500 g of beech wood raw material was cut and crushed to a particle size of less than 50 mesh, and then cleaned and purified;

[0109] II: Add the cleaned beech wood powder into a solution containing laccase (sodium citrate buffer with a pH of 4.0) at a solid-liquid ratio of 1:5 g / mL, place the solution in a 45°C water bath for heating and stirring, and filter out the beech wood powder after 24 hours of enzymatic hydrolysis.

[0110] III: The beech wood powder after enzymatic pretreatment is dried and then placed in a large atmosphere furnace for high-temperature carbonization at 1400°C for 3 hours in a nitrogen atmosphere. The carbonized powder is then acid-washed and dried with a 1 mol / L hydrochloric acid solution to obtain high-performance biomass hard carbon.

[0111] Comparative Example 9

[0112] The preparation process of Comparative Example 9 is basically the same as that of Comparative Example 8, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 7.0.

[0113] Comparative Example 10

[0114] The preparation process of Comparative Example 10 is basically the same as that of Comparative Example 8, except that the pH of the enzymatic hydrolysis environment in step II of preparing high-performance biomass hard carbon is 8.0.

[0115] Furthermore, the biomass hard carbon material prepared in the above embodiments and comparative examples was prepared into a negative electrode slurry according to a mass ratio of hard carbon: conductive agent: binder (8:1:1), and coated on a current collector (copper foil). The slurry was then dried and sliced, and C2032 button batteries were assembled in a glove box and placed in a Xinwei battery test channel after standing for 12 hours for relevant sodium storage performance tests.

[0116] Depend on Figure 1 From the first charge-discharge curve, it can be seen that the high-performance biomass hard carbon material prepared by cellulase hydrolysis for 48 hours in Example 4 has a first coulombic efficiency of 92% and a first-cycle charge capacity of 366 mAh / g at a current density of 20 mA / g;

[0117] Depend on Figure 2 From the first charge-discharge curve, it can be seen that the high-performance biomass hard carbon material prepared by hemicellulase hydrolysis for 24 hours in Example 8 has a first coulombic efficiency of 95% and a first cycle charge capacity of 351 mAh / g at a current density of 20 mA / g;

[0118] Depend on Figure 3 From the first charge-discharge curve, it can be seen that the high-performance biomass hard carbon material prepared by cellulase hydrolysis for 48 hours in Example 13 has a first coulombic efficiency of 93% and a first cycle charge capacity of 356 mAh / g at a current density of 20 mA / g;

[0119] Depend on Figure 4 From the first charge and discharge curve, it can be seen that the high-performance biomass hard carbon material prepared in Comparative Example 1 has a first coulombic efficiency of 87% and a first cycle charge capacity of 312 mAh / g at a current density of 20 mA / g;

[0120] The test results of the embodiments and comparative examples are summarized in the following table:

[0121]

[0122]

[0123] It can be seen from Examples 1-15 and Comparative Example 1 that the high-performance biomass hard carbon obtained in Examples 4, 8, and 13 has significantly improved reversible charging capacity and first-cycle coulomb efficiency compared to Comparative Example 1 without bio-enzyme pretreatment. Among them, Example 4 is the optimal embodiment for cellulase pretreatment, with a reversible capacity of 366mAh / g and a first-cycle coulomb efficiency of 92%; Example 8 is the optimal embodiment for hemicellulase pretreatment, with a reversible capacity of 351mAh / g and a first-cycle coulomb efficiency of 95%; Example 13 is the optimal embodiment for laccase pretreatment, with a reversible capacity of 356mAh / g and a first-cycle coulomb efficiency of 93%. Furthermore, the present invention combines the optimal treatment and regulation of the three biomass enzymes, and sequentially treats the biomass raw materials with cellulose and hemicellulose. The lignin content is adjusted, and the final Example 16 is prepared. The high-performance biomass hard carbon material prepared after adjustment and optimization of the three components has a reversible capacity of 383mAh / g and a first-cycle coulombic efficiency of 90%, which is greatly improved compared with Comparative Example 1. This directly indicates that the content of the three major elements in the biomass precursor is closely related to the performance of the biomass-based hard carbon prepared therefrom. By integrating the bio-enzyme pretreatment process and adjusting the relative content of the three major elements, biomass-based hard carbon materials with excellent performance can be prepared.

[0124] At the same time, by further comparing the enzymatic hydrolysis environment in combination with Comparative Examples 2-10, it can be seen that after changing the pH, the effect of the enzymatic pretreatment is significantly different. When the pH of the enzymatic pretreatment solution is changed to a more acidic environment (pH = 4.0) and when the pH of the enzymatic pretreatment solution is changed to an alkaline environment (pH = 8.0), the performance of Comparative Examples 2, 5, 8 and Comparative Examples 4, 7, and 10 is significantly reduced compared with the optimal Examples 4, 8, and 13, indicating that in a more acidic environment and an alkaline environment, the biological enzyme pretreatment is significantly inactivated, and the regulation effect of the cellulose, hemicellulose, and lignin components in the biomass raw materials cannot be achieved. When the pH of the enzymatic pretreatment solution is changed to a neutral environment (pH = 7.0), the performance of Comparative Examples 2, 5, 8 and 3, 6, and 9 decreases compared to the optimal Examples 4, 8, and 13, but is significantly improved compared to Examples 1, 6, and 10, indicating that the bio-enzyme pretreatment can be effective in a neutral environment, but the efficiency is low, which greatly increases the time cost of biomass pretreatment. Therefore, the optimal bio-enzyme pretreatment environment is determined to be a weakly acidic environment with a pH of 6.0.

[0125] The above experimental results prove that the bio-enzyme pretreatment method adopted by the present invention can efficiently and stably regulate the relative contents of cellulose, hemicellulose and lignin components in the biomass precursor, so that the three maintain a balance during the carbonization process, thereby preparing high-performance biomass hard carbon with suitable structure and excellent performance. The method of the present invention is not only green and efficient in process and has low environmental toxicity, but also can greatly improve the reversible capacity and first-cycle coulomb efficiency of the biomass hard carbon in the prepared product.

[0126] The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. It should be pointed out that for ordinary technicians in this technical field, any changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing high-performance biomass hard carbon by enzyme pretreatment, characterized in that: The steps include: I: cutting and crushing the biomass raw materials, and then cleaning and purifying them; II: adding the washed biomass powder into a solution containing biological enzymes for enzymatic pretreatment; III: The biomass powder after enzymatic pretreatment is filtered out, dried and then carbonized at high temperature, and then the carbonized powder is acid-washed and then dried to obtain high-performance biomass hard carbon.

2. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step I, the biomass raw material is at least one of bamboo, beech, eucalyptus, straw, rice stalk, and fruit shell.

3. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step II, the biological enzyme used includes at least one of cellulase, hemicellulase, laccase, pectinase, catalase and amylase.

4. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step II, the biological enzyme needs to be dissolved in a corresponding culture solution, and the solution is a sodium citrate buffer solution with a pH between 4 and 8, preferably a pH of 5.0-6.

0.

5. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step II, the enzymolysis temperature is 25°C-60°C, preferably 45°C; the enzymolysis time is 6h to 72h.

6. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step II, the enzymatic pretreatment is to use cellulase, hemicellulase and laccase for enzymatic treatment in sequence, and the conditions for enzymatic hydrolysis of cellulase, hemicellulase and laccase are: enzymatic hydrolysis at 25° C.-60° C. for 6 h-72 h.

7. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step II, the enzymatic pretreatment environment needs to control the solid-liquid ratio, which is 1:3 to 1:10 g / mL, and the preferred solid-liquid ratio is 1:5 g / mL.

8. The method for preparing high-performance biomass hard carbon by enzyme pretreatment according to claim 1, characterized in that: In step III, the high-temperature carbonization temperature is 1200-1500° C., the carbonization time is 2-6 hours, and the carbonization atmosphere is one or more of nitrogen and argon; preferably, the carbonization temperature is 1400° C., and the carbonization time is 3 hours.

9. A high-performance biomass hard carbon, characterized in that: The high-performance biomass hard carbon is prepared by the bio-enzyme pretreatment preparation method as described in any one of claims 1 to 8.

10. The use of the high-performance biomass hard carbon according to claim 9, characterized in that: The high-performance biomass hard carbon material is used as the negative electrode of the sodium ion battery.

Citation Information

Patent Citations

  • Specialized activated carbon derived from pretreated biomass

    CN108136453A

  • Wood biomass-based porous carbon material prepared by high-temperature hydrothermal assisted cellulase hydrolysis, and application and method thereof

    CN113247893A

  • Enzymolysis modified starch-based hard carbon material as well as preparation method and application thereof

    CN118183699A

  • Method for producing carbon material, carbon material, and secondary battery

    JP2014205596A

  • Immobilized enzymes and uses thereof

    US20100209968A1

Cited By

  • High-performance biomass hard carbon, and preparation method therefor by means of bio-enzyme pretreatment and use thereof

    WO2026130585A1